Numerical Theoretical Study on Mechanical Properties of New Reinforced Tenon Precast Shear Walls - Wei Chen; Qing Wu; Dongyue Wu; Longji Dang; Feifei Jiang (Advances in Civil Engineering)
Precast construction technologies have several advantages in industrialized production, such as quality control and energy conservation. However, the joint interface slippage between the precast components causes detrimental effect on the mechanical properties, such as dowel shear stress on the connecting steel bars, which strictly restricts the development of assembly technology in aseismic structure. In order to eliminate the horizontal slippage along the assemble joint and optimize the mechanical performance of horizontal joint connections, a new reinforced tenon joint precast shear wall is proposed in this paper. Finite element numerical simulations are conducted on three reinforced tenon joint specimens and a reference specimen to understand the mechanical properties of the reinforced tenon and boundary confinement components of shear wall. The load-displacement curves, the equivalent plastic strain distribution diagram, and the concrete damage distribution diagram are obtained. It is found that the boundary components provide bending strength and the reinforced tenon can reduce the harmful influence of dowel-action shear stress on longitudinal connecting reinforcements. Therefore, the bending and shearing forces are separated at the joint interface. Based on the numerical simulation results and the calculation theory of normal section bearing capacity, the theoretical calculation bending capacity formula of reinforced tenon precast shear wall is established. The obtained calculation results are in good agreement with the simulation results and can accurately reflect the bending capacity of the jointed interface.